A case of primary adenocarcinoma of Meckel’s diverticulum presenting as ovarian mass and literature review - Gupta, Arnab; Inderdeep, Singh; Sudip, Haldar; Biman, Chakraborty (Indian Journal of Case Reports, 2021)
Meckel’s diverticulum (MD) is the most common congenital anomaly affecting the gastrointestinal tract. It is located on the anti-mesenteric border of the small intestine and occurs due to incomplete obliteration of the omphalomesenteric duct during embryogenesis. Tumors, particularly cancers, are rare complications of MD. Carcinoids are the most common malignancies in this site. Adenocarcinomas are extremely rare and carry a poor prognosis. Here, we present the case of adenocarcinoma of MD presenting as Krukenberg tumor in a 42-year-old lady and causing a diagnostic dilemma. Pelviabdominal examination revealed large bilateral adnexal masses along with ascites and computed tomography-guided fine-needle aspiration cytology from the right adnexal mass was suggestive of adenocarcinoma. At exploratory laparotomy, a MD was found with hard intramural growth palpable at the tip of MD adnexal deposits and omental caking. Immunohistochemistry revealed CK 7- and CK 20+ve and also CDX2 positive. The rarity of presentation of bilateral adnexal mass due to primary adenocarcinoma of MD urges us to report this case.